Perancangan User Interface Website Laboratorium Analisis Perancangan Kerja Dan Ergonomi Universitas Telkom Dengan Metode Double Diamond - Santoso, Diesya Latifa; Mufidah, Ilma; Iqbal, Muhammad (Universitas Pahlawan Tuanku Tambusai, 2024)
The APK&E Laboratory at Telkom University is facing the problem of 116 out of 486 practitioners not graduating in 2022, due to a lack of understanding of practicum requirements informed through a Facebook group. To overcome this, the research aims to design a website user interface mockup as a more effective information dissemination medium. The Double Diamond method was used, consisting of the discover, define, develop, and deliver phases. In the discover and define phases, in-depth analysis through interviews and surveys identified user needs and evaluated existing means of information dissemination. In the develop and deliver phase, a website mockup was designed which was tested for ease of use. The mockup design included features such as an easy-to-navigate main page, structured practicum information, and information upload time settings. Usability testing with the System Usability Scale (SUS) showed a score of 88, categorized as